A Set-Up of 7 Laser Triangulation Sensors and a Draw-Wire Sensor for Measuring Relative Displacement of a Piston Rod Mechanical Lead-Through Transmission in an Offshore Wave Energy Converter on the Ocean Floor. (5th March 2012) - Strömstedt, E.; Svensson, O.; Leijon, M.
Abstract : A concept for offshore wave energy conversion is being developed at the Swedish Centre for Renewable Electric Energy Conversion at Uppsala University in Sweden. The wave energy converter (WEC) in focus contains a piston rod mechanical lead-through transmission for transmitting the absorbed mechanical wave energy through the generator capsule wall while preventing seawater from entering the capsule. A set-up of 7 laser triangulation sensors has been installed inside the WEC to measure relative displacement of the piston rod and its corresponding seal housing. A draw-wire sensor has also been set up to measure translator position and the axial displacement of the piston rod. The paper gives a brief introduction to the Lysekil research site, the WEC concept, and the direct drive of WEC prototype L2. A model of operation for the piston rod mechanical lead-through transmission is given. The paper presents sensor choice, configuration, adaptation, mounting, and measurement system calibration along with a description of the data acquisition system. Results from 60 s measurements of nominal operation two months apart with centered moving averages are presented. Uncertainty and error estimations with statistical analyses and signal-to-noise ratios are presented. Conclusions are drawn on the relative motions of the piston rod and the seal housing under normal operating conditions, and an assessment of the applicability of the measurement system is made.